Interleukin-36 Cytokines in Infectious and Non-Infectious Lung Diseases - Peñaloza, Hernán F.; van der Geest, Rick; Ybe, Joel A.; Standiford, Theodore J.; Lee, Janet S. (Frontiers in Immunology, 2021)
The IL-36 family of cytokines were identified in the early 2000’s as a new subfamily of the IL-1 cytokine family, and since then, the role of IL-36 cytokines during various inflammatory processes has been characterized. While most of the research has focused on the role of these cytokines in autoimmune skin diseases such as psoriasis and dermatitis, recent studies have also shown the importance of IL-36 cytokines in the lung inflammatory response during infectious and non-infectious diseases. In this review, we discuss the biology of IL-36 cytokines in terms of how they are produced and activated, as well as their effects on myeloid and lymphoid cells during inflammation. We also discuss the role of these cytokines during lung infectious diseases caused by bacteria and influenza virus, as well as other inflammatory conditions in the lungs such as allergic asthma, lung fibrosis, chronic obstructive pulmonary disease, cystic fibrosis and cancer. Finally, we discuss the current therapeutic advances that target the IL-36 pathway and the possibility to extend these tools to treat lung inflammatory diseases.